(untitled) (Ameghiniana, 2013)
A new petrified Nothofagus wood have been described here from Miocene sediments near General Roca. The most important anatomical characters are: growth rings evident, diffuse porosity with a tendency to ring porosity; vessels very numerous and small commonly in radial multiples 3-5, sometimes up to 11 pores, few solitaries and in clusters; perforation plates simple, intervessel pitting predominantly alternate with an opposite tendency; tyloses and spiral thickenings present in almost all the vessels. The parenchyrna is sparsely diffuse apotracheal including large crystal strands, the rays are mostly 2-seriate, sometimes 1 and 3-seriate with dark contents and the fibres have moderately thickened walls. Comparisons with living and fossil representatives of Nothofagus have been made, concluding that Nothofagoxylon menendezii has differences with all of them being more similar with the argentine species Nothofagus obliqua from Neuquen province.